Use FOIL to solve the problem (3x-2)(2x-3) first ?

1 Answer
Feb 9, 2018

6x^2-13x+6 is the final answer :)

Explanation:

There's a shortcut you can use here, known as the " FOIL " method (that stands for F irst, O uter, I nner, L ast.). The product of two binomials is the sum of four simpler products.

The word FOIL is an acronym for the four terms of the product.



enter image source here



Firsts: " " 3x\times 2x=6x^2
Outsides: " " 3x\times -3=-9x
Insides: " " -2\times 2x=-4x
Lasts: " " -2\times -3=6

Add all these up, and you'll get the answer:

=6x^2+(-9x)+(-4x)+6

=6x^2-9x-4x+6

=6x^2-13x+6